Urban green and grey space in relation to respiratory health in children. Issue 6 (22nd June 2017) - Tischer, Christina; Gascon, Mireia; Fernández-Somoano, Ana; Tardón, Adonina; Lertxundi Materola, Aitana; Ibarluzea, Jesus; Ferrero, Amparo; Estarlich, Marisa; Cirach, Marta; Vrijheid, Martine; Fuertes, Elaine; Dalmau-Bueno, Albert; et al.
We assessed the effect of three different indices of urban built environment on allergic and respiratory conditions. This study involved 2472 children participating in the ongoing INMA birth cohort located in two bio-geographic regions (Euro-Siberian and Mediterranean) in Spain. Residential surrounding built environment was characterised as 1) residential surrounding greenness based on satellite-derived normalised difference vegetation index (NDVI), 2) residential proximity to green spaces and 3) residential surrounding greyness based on urban land use patterns. Information on wheezing, bronchitis, asthma and allergic rhinitis up to age 4 years was obtained from parent-completed questionnaires. Logistic regression and generalised estimating equation modelling were performed. Among children from the Euro-Siberian region, higher residential surrounding greenness and higher proximity to green spaces were negatively associated with wheezing. In the Mediterranean region, higher residential proximity to green spaces was associated with a reduced risk for bronchitis. A higher amount of residential surrounding greyness was found to increase the risk for bronchitis in this region. Associations between indices of urban residential greenness and greyness with respiratory diseases differ by region. The pathways underlying these associations require further exploration. Associations betweenrespiratory health and urban residential greenness and greyness differ by geographic region http://ow.ly/pnGJ30bqBn1